Assess the Efficacy of Health Information on Knowledge Regarding Post Dialysis Home Care among Caretakers of Haemodialysis Patients - et al., Yogesh A. Jadhav (International Journal of Advanced Science and Technology, 2020)
Objectives were to assess the level of knowledge regarding post dialysis home care among caretakers of patients undergoing hemodialysis, to evaluate the effectiveness of health information on post dialysis home care among caretakers of patient undergoing hemodialysis and to determine knowledge with the selected demographic variables among caretakers of patient undergoing hemodialysis. Method: one group pretest posttest design was used to conduct the study among caretakers of hemodialysis patients and totally 50 caretakers were selected by Purposive Sampling technique. Ethical permission was obtained before the data collection. After obtaining permission from the setting, the caretakers were asked their willingness to participate in the study and informed consent was obtained. The demographic variables were collected by using structure interview questionnaire. During pre-test the Caretakers knowledge of post dialysis home care was measured by multiple choice questions, which had 30 questions for 15 minutes. Then the subject received Health information Programme regarding post dialysis home care for 30 minutes. On 7th day post-test was done by researcher as like pre-test to assess the effectiveness of Health information Programme on Knowledge regarding post dialysis home care among Caretakers of Chronic Renal Failure patients undergoing hemodialysis. Results: There was a significant difference between pre-test and post-test scores on knowledge regarding Post Dialysis Home Care among Caretakers. Calculated value of ‘t’ was greater than tabulated value t at 5% level of significance. Conclusions: The educational programme regarding post dialysis home care is a vital role in improving caretaker’s knowledge of post dialysis home care.